The turkish petroleum law on the way of the european union - Armağan, Özlem İnanç (My University, 2008)
AVRUPA BİRLİĞİ YOLUNDA TÜRK PETROL HUKUKU Tezin amacı Avrupa Birliği’nin enerji ve petrol politikalarında Türkiye’nin günümüzdeki ve gelecekteki rolünü sergilemek ve bu amaçla Avrupa Birliği ve Türk petrol hukuku tarihçesine dair bilgiler ve günümüz düzenlemelerini açıklamaktır Petrol tüketimi sürdürülebilir kalkınma açısından değerlendirilmektedir. Bu tez günümüz ve gelecekteki enerji kaynağı stratejileri ve alternatiflerini ancak özellikle petrol konusunu incelemektedir. Avrupa Birliği ve tabii ki Türkiye gelişmesini sürdürebilmek için sürekli enerjiye ihtiyaç duymaktadır. Türkiye doğal konumu sebebiyle Avrupa Birliği için doğu ve dünyanın bir numaralı petrol kaynağı ülkelerinden köprü durumundadır. Bununla bağlantılı olarak bu tez özellikle Türkiye ve Avrupa Birliği’ndeki özellikle petrol aranması, çıkartılması ve piyasaya arzı konusunda mevcut ve olası yasal düzenlemelere ilişkindir. Sonuç olarak tezin içeriği ve amacı, Türkiye için mevcut ve potansiyel çalışmalar ışığında Türkiye’nin petrol potansiyelini gerçekleştirebilecek olursa, arz güvenliğini sağlayarak ulusal ve politik kontrolünü sağlayacağı varsayımından hareketle; Avrupa Birliği ve Türkiye’deki petrol konusundaki yasal düzenlemelerin incelenmesidir. Enerji Hukuku, Petrol hukuku, Petrol Politikaları.

THE TURKISH PETROLEUM LAW ON THE WAY OF THE EUROPEAN UNION The purpose of this thesis is to highlight Turkey's current and potential role in energy policies of the European Union and giving details on European Union’s and also Turkey’s petroleum arrangements from the historical perspective and also via recent legislations. Petroleum consumption may be dealt within the context of sustainable development. This thesis examines recent and projected energy source patterns of existing energy strategies and their renewable alternatives but especially the subject of petroleum . As a one of the leading market, EU and also Turkey needs continuous energy in order to keep on its development. And Turkey is geographically a natural gateway through which the EU can access oil from east and many of the world's primary oil supplier countries. This thesis is mainly about legal arrangements on exploration, production and distribution of petroleum. To sum up, if Turkey can realize petroleum potential, it can have national and political control in order to ensure security of supply and indeed it is the key to economic development and driving force behind its modern society and important role in the world / EU politics.. Energy Law, Petroleum Law, Petroleum Policy
Keywords: Avrupa Birliği Hukuku; Türkiye_Petrol_Hukuk